Studi in Silico dari Senyawa Turunan Flavonoid pada Bahan Alam sebagai Terapi Antinyeri dan Inflamasi dalam Menghambat COX 2 - Balqis Khansa Rahmatillah; Anisa Humaira Pelupessy; Amelia Putri; Aisril Eka Pertiwi; Afiq Rabbani Majid; Muhamad Iqbal Rhamadianto (Lembaga Pengembangan Kinerja Dosen, 2025)
Inflammation is the body's natural biological response to tissue injury, infection, or other harmful stimuli. Inflammatory processes play an important role in maintaining the body's homeostasis, but excessive or chronic inflammation can trigger various degenerative diseases, including arthritis, cancer, and cardiovascular disorders. One of the main mediators of inflammation is the enzyme cyclooxygenase-2 (COX-2), which is in charge of converting arachidonic acid into pro-inflammatory prostaglandins. Inhibition of COX-2 activity is an important strategy in controlling inflammation. Selective COX-2 inhibitors (Coxibs) have been developed to reduce the gastrointestinal side effects commonly caused by conventional nonsteroidal anti-inflammatory drugs (OAINS). However, the use of Coxibs still poses a significant cardiovascular risk, so the search for alternatives from natural ingredients continues. Flavonoid compounds, which are abundant in fruits, vegetables, teas, and spices, show great potential as natural COX-2 inhibitors. Flavonoids have a polyphenol structure that allows for strong interactions with COX-2 active sites through hydrogen bonding and hydrophobic forces. This study is a literature review that examines the potential of flavonoids from natural ingredients as COX-2 inhibitors based on an in silico approach. This method was carried out through a literature search on the Google Scholar database using the keywords